A case report: adenosine triggered myocardial infarction during myocardial perfusion stress test imaging in a diabetic patient. Issue 4 (30th April 2021) - de Mulder, Maarten; van Gameren, Menno; van Asperen, Eric A; Meuwissen, Martijn
Abstract: Background: Myocardial perfusion imaging (MPI) using single-photon emission computed tomography (SPECT) can in general be used safely in daily clinical practice. However, under the right circumstances, it can lead to serious complications. Case summary: A 68-year-old female patient with diabetes and a history of inferior ST-elevation myocardial infarction 8 years earlier, visited our outpatient clinic with atypical chest discomfort. In order to assess whether this is due to myocardial ischaemia, MPI-SPECT was ordered. As it was suspected she would not achieve sufficient exercise levels, pharmacologic stress using adenosine was arranged. During the scan, she developed acute myocardial infarction. Subsequent urgent coronary angiography demonstrated a subtotal stenosis in the proximal left anterior descending coronary artery which was successfully stented. She was still free from angina 4 months later. Discussion: The combination of a reduced systemic and coronary perfusion pressure in the presence of an exhausted coronary autoregulation, may be a starting point for local geometrical changes that initiate the classic cascade of thrombus formation and acute occlusion of coronary arteries during MPI-SPECT. This illustrates the need for continuous patient and electrocardiogram monitoring.